The Relationship between Health Service Quality and Outpatient Satisfaction Level at Kenangan Health Center, Deli Serdang Regency - Ivan Elisabeth Purba; Taruli Rohana Sinaga; Rahmat Alyakin Dachi; Helvinus Laia (TOUR HEALTH JOURNAL, 2022)
Purpose: Quality of service is a form of patient assessment of the level of service received with the expected level of service. Quality service gives satisfaction to its users. Patient satisfaction is a form of reaction as an attitude that arises as a result of the evaluation process within the individual which then provides conclusions on the stimuli that can be in the form of good or bad, positive, negative, pleasant or unpleasant or emotional ratings related to the quality of services provided by the Puskesmas and patient expectations of the service. This study aims to determine the relationship between the quality of health services and the satisfaction level of outpatients at the Kenangan Health Center, Deli Serdang Regency in 2022. Method: The correlation analytic study design used a cross sectional approach. The population in this study were outpatients at the Kenangan Health Center, Deli Serdang Regency, from January to May 2022, with an average of 869 patients per month. The sampling technique used the Purpose Sampling technique so that the number of samples in this study were 90 people. The instruments used were questionnaires, the data were analyzed using the Chi-Square test. Results: The results showed that the quality of outpatient services at the Kenangan Health Center in Deli Serdang Regency in 2022 assessed the quality of health services as not good at 51.1% with a total of 46 respondents and outpatient satisfaction at the Kenangan Health Center in Deli Serdang Regency in 2022 which assessed patient satisfaction was not satisfied by 53.3% with a total of 48 respondents, there is a significant relationship between the relationship between the quality of health services and the level of outpatient patient satisfaction at the Kenangan Health Center, Deli Serdang Regency, in 2022 (p value = 0.000 <0.05). Disscusion and Conclusion: Suggestions to the Kenangan Health Center in Deli Serdang Regency for service workers to further increase empathy for patients so that patients feel really cared for by officers so they feel satisfied with the services provided.